Practical contouring guidelines with an MR-based atlas of brainstem structures involved in radiation-induced nausea and vomiting. (January 2019) - Beddok, Arnaud; Faivre, Jean-Christophe; Coutte, Alexandre; Guévelou, Jennifer Le; Welmant, Julien; Clavier, Jean-Baptiste; Guihard, Sébastien; Janoray, Guillaume; Calugaru, Valentin; Pointreau, Yoann; Lacout, Alexis; Salleron, Julia; et al.
Highlights: Nausea and vomiting: a new side effect of radiotherapy for head and neck carcinomas. Irradiation of some structures of the brainstem could explain this new side effect. A new and reproducible atlas to accurately delineate these brainstem structures. Abstract: Background and purpose: The objective of this project was to define consensus guidelines for delineating brainstem substructures (dorsal vagal complex, including the area postrema) involved in radiation-induced nausea and vomiting (RINV). The three parts of the brainstem are rarely delineated, so this study was also an opportunity to find a consensus on this subject. Materials and methods: The dorsal vagal complex (DVC) was identified on autopsy sections and endoscopic descriptions. Anatomic landmarks and boundaries were used to establish radio-anatomic correlations on CT and Magnetic Resonance Imaging (MRI). Additionally, delineation of RINV structures was performed on MRI images and reported on CT scans. Next, guidelines were provided to eight radiation oncologists for delineation guidance of these RINV-related structures on DICOM-RT images of two patients being treated for a nasopharyngeal carcinoma. Interobserver variability was computed. Results: The DVC and the three parts of the brainstem were defined with a concise description of their main anatomic boundaries. The interobserver analysis showed that the DVC, the midbrain, the pons, and the medulla oblongata delineations were reproducible with KI = 0.72, 0.84, 0.94 and 0.89, respectively. The Supplemental Material section provides an atlas of the consensus guidelines projected on 1-mm MR axial slices. Conclusions: This RINV-atlas was feasible and reproducible for the delineation of RINV structures on planning CT using fused MRI. It may be used to prospectively assess dose–volume relationship for RINV structures and occurrence of nausea vomiting during intracranial or head and neck irradiation.